2015
DOI: 10.1021/acs.analchem.5b02812
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Signal Amplification Assay for Mercury Ions Based on the Catalysis of Gold Amalgam

Abstract: Mercury is a major threat to the environment and to human health. It is highly desirable to develop a user-friendly kit for on-site mercury detection. Such a method must be able to detect mercury below the threshold levels (10 nM) for drinking water defined by the U.S. Environmental Protection Agency. Herein, we for the first time reported catalytically active gold amalgam-based reaction between 4-nitrophenol and NaBH4 with colorimetric sensing function. We take advantage of the correlation between the catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…10 These advantageous features encourage extensive exploration of the applications of nanozymes in diverse areas including biosensing, imaging, and therapeutics over the past few decades. 11,12 However, it remains challenging to obtain nanozymes that enhance the catalytic activity, which greatly limits the scope and performance of their applications. 1315 The typical approaches to promote the catalytic activity of nanozymes are to construct hybrid nanostructures or to combine the nanozymes with a natural enzyme.…”
mentioning
confidence: 99%
“…10 These advantageous features encourage extensive exploration of the applications of nanozymes in diverse areas including biosensing, imaging, and therapeutics over the past few decades. 11,12 However, it remains challenging to obtain nanozymes that enhance the catalytic activity, which greatly limits the scope and performance of their applications. 1315 The typical approaches to promote the catalytic activity of nanozymes are to construct hybrid nanostructures or to combine the nanozymes with a natural enzyme.…”
mentioning
confidence: 99%
“…In this study, Au NCs facilitate the reduction of Hg 2+ via surface‐capped citrate. The amalgam formation also indicates citrate‐capped Au NCs . The QY of Au NCs is ~10 % ( n = 3).…”
Section: Resultsmentioning
confidence: 98%
“…The results show that the fluorescence of Fe 3+ and Cr 3+ can be recovered after adding EDTA. The fluorescence response of Au NCs with Hg 2+ (Figure ) could not be recovered because of the formation of an amalgam . It is known that the Au surface has strong affinity for Hg 2+ .…”
Section: Resultsmentioning
confidence: 98%
“…Recently, many works have discovered that mercury ions could interact with other metal nanoparticles to form bimetallic NPs4748. In addition, it was also confirmed that the citrate around the surface of metal NPs was essential to promote the process of these combinations.…”
mentioning
confidence: 91%